Oral Health Service Use in Older Peruvians Before and During the COVID-19 Pandemic - Diego Azañedo; Fabriccio J. Visconti-Lopez; Akram Hernández-Vásquez (Elsevier, 2024)
ABSTRACT: Objectives: The aim of this work was to analyse inequalities in oral health services utilisation (OHSU) in older Peruvian adults through comparative analysis of the years 2019 and 2021. Methods: We conducted a secondary analysis of data from the 2019 and 2021 Demographic and Health Survey (ENDES). The outcome variable was OHSU by older Peruvian adults in the past year. We used Poisson generalised linear models adjusted for age and sex to assess changes in OHSU by sociodemographic characteristics. The Erreygers concentration index was used to describe the socioeconomic inequalities in OHSU. The contribution of each variable to inequalities was estimated by a decomposition analysis. Results: In 2021, OHSU probability amongst older Peruvian adults decreased by 37% compared to 2019. The decline was greatest in those aged 80 or older (51%), the lowest wealth quintile (47%), those with functional limitations (53%), and those whose native language is Quechua or other indigenous languages (47%). Surprisingly, we observed a reduction in OHSU inequalities (difference: −0.1074; P = .003) during the COVID-19 pandemic, particularly amongst rural residents (difference: −0.0771; P = .030), the lowest wealth quintile (difference: −0.0764; P = .020), and those with functional limitations (difference: −0.3665; P < .001). Poverty accounted for 73% of the inequality in 2021. Conclusions: The probability of OHSU has significantly decreased likely due to the COVID-19 pandemic. Paradoxically, we observed a reduction in OHSU inequalities during the pandemic, despite the known socioeconomic impact. However, further research is required to gain deeper understanding of this phenomenon.